Sociabilidades respeitadas: a participação dos idosos na implementação da Política Nacional do Idoso no município de São Carlos -SP - Emérito, Jamila Lopes Pereira (2006)
This work intended to avaluate the implications of “Old-aged National Politics – PNI” in the city of São Carlos, São paulo, in 2003 and 2004. The participation of technicians and the old-aged themselves in the local construction of this politics was investigated. It was done a qualitative avaluation, because it permitted a close relation among the subject of the research and also a more dense analysis of the social relation of the groups. Quantitative data were used for the analysis done. In order to get the informations, city places of oldaged representation were monitorred in a sistematic way, meanly the groups coordinated by the public manager responsible for PNI city implementation, represented by the city secretary for citzenship and social assistence and the city concil for old-aged, in function of the municipality of the public politics of social inclusion, where is inserted the PNI, according to 1988’s Constitution. It was demonstrated that old-aged en São Carlos – SP still don’t see themselves as constructers of old-aged politcs in the city and that this process is slow, gradual, but in this specific case, progressive. There’s a perception of PNI as a collective right under the obligation of the state. The participation of old-aged in groups organized by local society or the public manager operates initially for individual reasons and their envolvement as constructers of public politics oriented to stablish and reforce citzen’s rights, envolves, among all, the universilization and internalization of information and interation between different generations.